Conflicting opinions in connection with digital superintelligence - Ahmed Al-Imam; Marek A. Motyka; Mariusz Z. Jędrzejko (Institute of Advanced Engineering and Science, 2020)
In 1964, Nikolai Kardashev proposed the Kardashev scale, a system for measuring the extent of technological advancement of a civilization based on the magnitude of energy consumption. We are approaching an inevitable type-1 civilization, and artificial superintelligence superior to that of humans can concur with a higher-hierarchy Kardashev civilization. We aim to survey public opinions, specifically video gamers, worldwide compared to those in Poland, concerning artificial general intelligence and superintelligence. We implemented an amalgam of cross-sectional and longitudinal analyses of the database of literature and Google search engine. The geographic mapping of surface web users who are interested in artificial superintelligence revealed the top ten contributing countries: Iran, Mexico, Colombia, Brazil, India, Peru, South Africa, Romania, Switzerland, and Chile. Developing countries accounted for 54.84% of the total map. Polish people were less enthusiastic about artificial general intelligence and superintelligence compared with the rest of the world. Futuristic technological innovations imply an acceleration in artificial intelligence and superintelligence. This scenario can be pessimistic, as superintelligence can render human-based activities obsolete. However, integrating artificial intelligence with humans, via brain-computer interface technologies, can be protective. Nonetheless, legislation in connection with information technologies is mandatory to regulate upcoming digital knowledge and superintelligence.